Pengabdian Masyarakat Gabungan tentang Peningkatan Pengetahuan Kesehatan Gigi dan Mulut di SD Al-Marusiyah antara Institut Ilmu Kesehatan Bhakti Wiyata dengan Universiti Sains Malaysia - Nurmalasari, Afrida; Setiawan, Fery; Prakosa, Basma Rosandi; Chasanah, Niswatun; Rudy S.; Apriyono, Dwi Kartika; Suhartini; Yusof, Ainuddin Yushar (Fakultas Kedokteran Gigi, Universitas Jember, 2025)
Perception of oral hygiene has a major impact on life expectancy worldwide, but in middle-income countries it is a problem, where oral health problems in Indonesia affect as much as 57.6% of the population. A semi-experimental study was conducted on October 30, 2024 on students at Al-Marusiyah Elementary School, Kediri City, East Java, Indonesia. The study method was carried out offline (face-to-face) using a mixture of presentation media (power point) and booklets. The socialization participants were divided into two parts: pre-socialization (pre-test) and post-socialization (post-test). The socialization participants were given questions to assess their knowledge and perceptions of oral health before and after the socialization. Participants' knowledge was classified as sufficient, moderate, and low in understanding oral hygiene before and after the socialization. This counseling was carried out as part of a collaboration between the Faculty of Dentistry (FKG) of the Bhakti Wiyata Institute of Health Sciences (IIK) and the Faculty of Dentistry (FKG) of the University of Sains Malaysia (USIM). This counseling aims to improve dental health knowledge of students at Al-Marusiyah Elementary School so that it is hoped that it can reduce the DMF-t rate in students at Al-Marusiyah Elementary School.Keywords: Dental health; Oral health; Elementary school students; Faculty of Dentistry Institute Health Science Bhakti Wiyata; Faculty of Dentistry Universiti Sains Malaysia.